Matrixes least squares method: examples of its application in macroeconomics and TV-media business - Donchenko, Volodymyr; Nazaraga, Inna; Tarasova, Olga (Eastern-European Journal of Enterprise Technologies, 2014)
In the paper general framework of Least Square Method (LSM) on vectors and matrixes observation is represented. Also the results developing M-Ppi technique are submitted. Some principal examples are represented in the article. These examples illustrate the advantages of LSM in the case under consideration. General algorithm LSM with matrixes observations is proposed and described in step-by-step variant for linear and nonlinear scaled data. The examples of method applications in macroeconomics and TV-media business illustrate the advantages and capabilities of the method. Correspondent results are also represented below as well as illustration of its applications for predicting in macroeconomics of Ukraine and in estimating of TV audience. The proposed approach for finding predictive values indicators is competitive.